Increased mutation efficiency of CRISPR/Cas9 genome editing in banana by optimized construct - Sen Zhang; Shaoping Wu; Chunhua Hu; Qiaosong Yang; Tao Dong; Ou Sheng; Guiming Deng; Weidi He; Tongxin Dou; Chunyu Li; Chenkang Sun; Ganjun Yi; et al. (PeerJ, 2022)
The CRISPR/Cas9-mediated genome editing system has been used extensively to engineer targeted mutations in a wide variety of species. Its application in banana, however, has been hindered because of the species’ triploid nature and low genome editing efficiency. This has delayed the development of a DNA-free genome editing approach. In this study, we reported that the endogenous U6 promoter and banana codon-optimized Cas9 apparently increased mutation frequency in banana, and we generated a method to validate the mutation efficiency of the CRISPR/Cas9-mediated genome editing system based on transient expression in protoplasts. The activity of the MaU6c promoter was approximately four times higher than that of the OsU6a promoter in banana protoplasts. The application of this promoter and banana codon-optimized Cas9 in CRISPR/Cas9 cassette resulted in a fourfold increase in mutation efficiency compared with the previous CRISPR/Cas9 cassette for banana. Our results indicated that the optimized CRISPR/Cas9 system was effective for mutating targeted genes in banana and thus will improve the applications for basic functional genomics. These findings are relevant to future germplasm improvement and provide a foundation for developing DNA-free genome editing technology in banana.